Application Test Rhizobium and Trichoderma To The Growth and Yield Of Soybean (Glycine Max (L)) - Sutarman Sutarman; Meilani Fatimah (Universitas Muhammadiyah Sidoarjo, 2017)
The objective of the research was to know of the responses of the aplication Rhizobium of nodule root Soybean as well as nodule root Mimosa pudica and Trichoderma iso- late Tc-Jjr02. The research was conducted on the Green House Faculty of Agriculture, Muhammadiyah University of Sidoarjo, from Januari to Mei 2016. This research com- piled using a factorial randomized complete design which consists of 2 factors : factor I is application Rhizobium consisting of : R0 (withow Rhizobium), R1(Rhizobium of soy- bean), R2(Rhizobium of mimosa pudica). Factor II application Trichoderma consisting of : T0 (withow Trichoderma) and T1 (Trichoderma isolat Jati Jejer-02). Of these two factors obtained 6 treatment combinations and repeated 4 times. From the analysis of statisti- cal data shows that application Rhizobium on significant effect the amount of leaf age 40 HST and 60 HST as well as the number of pods, planting seed weight , weight of 100 seeds, and fresh weight of plant root nodules. Application Rhizobium significantly affected the wet weight of stover. Trichoderma isolate Jati Jejer-02 capable symbio- sis with the plant so that the very significant effect on plant height age 7 HST and the amount of leaf age 20 HST. As well as the interaction between application Rhizobium and Trichoderma isolates significantly affected the number of pods plant.